Syphilis in Pregnancy: Exploring the prevalence and vertical transmission prevention cascade of syphilis using routinely collected electronic health data, Cape Town Metropolitan District, 2017–2022 - Gammon, Jessica (Department of Public Health and Family Medicine, 2025)
Introduction: Congenital Syphilis (CS), an important cause of perinatal morbidity and mortality, is notifiable in South Africa. CS results from vertical transmission of inadequately treated syphilis in pregnancy, a treatable sexually transmitted infection caused by Treponema pallidum. Gaps in our understanding of syphilis epidemiology exist amidst concerns of penicillin stockouts increasing CS cases. We evaluated current management and outcomes of syphilis in pregnancy in Cape Town. Methods: We retrospectively reviewed routinely collected electronic health data on a pregnant cohort and their infants from the Western Cape Provincial Health Data Centre. Clinical administration data, pharmacy and laboratory data were collated for patients identified as pregnant between January 2017 and December 2022. Pregnant women's laboratory TPAb (Treponema pallidum antibody) and RPR (rapid plasma reagin) results were reviewed. Results: 419 376 pregnancies were identified, resulting in 425 128 outcomes. 47% of pregnancies had a documented laboratory syphilis test, with 6812 (1.6%) of total pregnancies testing RPR positive. A total of 996 infants had a positive RPR, with a RPR seropositivity in infants of 267 per 100 000 live births. 636 (64%) of these infants were born to mothers who had tested positive for syphilis in pregnancy, and the remainder were either born to mothers who did not have a lab test for syphilis in pregnancy, or who had screened negative for syphilis in pregnancy. The proportion of seropositive pregnancies increased over time from 764 (1.2%) in 2017 to 1324 (1.9%) in 2022. Testing practices differed between geographic service areas with some doing laboratory tests for syphilis for all pregnancies and others doing confirmatory laboratory tests only after positive point-of-care treponemal tests. Of the syphilis seropositive pregnancies, 69% had no electronic evidence of appropriate treatment. 28% had recorded benzathine benzylpenicillin; 3% received amoxicillin with enzyme inhibitor; <1% received ceftriaxone. Only 23% of syphilis-positive women had a follow-up RPR titre. The risk of adverse pregnancy outcomes was higher among syphilis seropositive compared to seronegative women; neonatal deaths RR 1.91 (95% CI 1.53-2.38) and RR of stillbirths 2.52 (95% CI 2.25, 2.82). The risk of adverse perinatal outcomes was higher in those with high-titre active syphilis than low-titre syphilis. Conclusion: Routine electronic health data can provide oversight of CS prevention. Electronic capturing of pharmacy data is suspected to be incomplete and requires independent verification. There is an increasing prevalence trend of syphilis in pregnancy, resulting in preventable stillbirths and neonatal deaths. Increasing syphilis prevalence requires a public health response to ensure adequate treatment and repeat RPR titres to monitor response. Cases treated with an alternative regimen should be audited to assess outcomes. RPR seropositivity in infants is higher than national estimates and is likely an underestimate.